Be like a panda: reconstructing national identities through China's iconic species - Guo, Yulei; Fennell, David; Fennell, Sam (Frontiers in Sustainable Tourism, 2023)
Despite lacking clear historical significance, the appeal pandas have to the people of China has played an integral role in the emergence of the country's cultural identity and ideals. Few studies have explored the giant panda due to the ongoing dialogue between the West and China, which, according to Edward Said, is permeated with imperialist, colonial, and orientalist flavours. In 1869, the French missionary Armand David encountered a dead specimen of a giant panda in Baoxing, Sichuan, which sparked the beginning of this dialogue. David shipped the skin to Paris, where the animal was named and aesthetically recreated for the first time for Western audiences. In this paper, we approach the giant panda as a dark tourism attraction embodying a process of making and remaking Chinese national identities over the past two centuries. Using "virtual curating" to study the Giant Panda Museum located at the Chengdu Research Base of Giant Panda Breeding, we demonstrate that the giant panda, which has achieved iconic status in China, represents a national history that is dark, backward, and based on suffering and death. We argue that understanding the giant panda's history as a dark tourism attraction provides an ethical vantage point from which to perceive tourist-panda relationships.